IMPROVEMENT OF TEACHER WORK PRODUCTIVITY THROUGH STRENGTHENING COMMITMENT TO PROFESSIONALISM AND SUPERVISION OF SCHOOL PRINCIPALS USING CORRELATIONAL STATISTICAL ANALYSIS AND SITOREM METHODS - Eka Suhardi; Atep Yulia Nugraha; Soewarto Hardhienata (UNIVERSITAS PAKUAN, 2020)
Teacher work productivity can affect the progress of the quality of learning in schools. From the initial survey, it is seen that the work productivity of teachers, especially private junior high school teachers, has not been as expected, meaning